##### Find d^2y/dx^2 of 3x=y^2-x^2

label Calculus
account_circle Unassigned
schedule 1 Day
account_balance_wallet \$5

Given 3x = y^2 - x^2 , find d^2y/dx^2

SHOW ALL WORK

Oct 3rd, 2015

3x = y^2 - x^2

Now

y^2 = x^2 + 3x

Taking derivative w.r.t x, then

d/dx(y^2) = d/dx(x^2 + 3x)

2y dy/dx = 2x + 3

Now

dy/dx = (2x + 3)/2y

As

y = √ (x^2 + 3x) so

dy/dx = (2x + 3)/(√(x^2 + 3x))

Again taking derivative w.r.t x, we get

d/dx(dy/dx) = d/dx[ (2x + 3) / √(x^2 + 3x) ]

Using the rule of d/dx(u/v) = [v*d/dx(u) - u*d/dx(v)] / v^2

d^2 y/dx^2 = [ √(x^2 + 3x) * d/dx(2x + 3) - (2x + 3) * d/dx(√(x^2 + 3x)) ] / (√x^2 + 3x)^2

= [ 2*(√x^2 + 3x) - (2x + 3)(1/2 *√(x^2 + 3x) * (2x + 3)) ] / (x^2 + 3x)

= [ 2√(x^2 + 3x) - (2x + 3)^2 / 2√(x^2 + 3x) ] / (x^2 + 3x)

= [ {4(x^2 + 3x) - (2x + 3)^2} / 2√(x^2 + 3x) ] / (x^2 + 3x)

= (4x^2 + 12x - 4x^2 - 9 - 12x) / (x^2 + 3x) * 2√(x^2 + 3x)

= - 9 / 2(x^2 + 3x)^3/2

Hence         d^2 y/dx^2 = - 9 / 2(x^2 + 3x)^3/2

Sep 22nd, 2015

It says in my textbook

Sep 22nd, 2015

It says in my textbook

Sep 22nd, 2015

okay the answer we got is - 9 / 4(x^2 + 3x)^3/2

And we also know that

x^2 + 3x = y^2

So put the value of x^2 + 3x in the answer, we get

- 9 / 4(y^2)^3/2

- 9 / 4(y^2*^3/2)

- 9 / 4(y^3)

- 9 / 4y^3

Hence

Sep 22nd, 2015

Oh okay, thanks a bunch!

Sep 22nd, 2015

3x = y^2 - x^2

Now

y^2 = x^2 + 3x

Taking derivative w.r.t x, then

d/dx(y^2) = d/dx(x^2 + 3x)

2y dy/dx = 2x + 3

Now

dy/dx = (2x + 3)/2y

As

y = √ (x^2 + 3x) so

dy/dx = (2x + 3)/(2√(x^2 + 3x))

Again taking derivative w.r.t x, we get

d/dx(dy/dx) = d/dx[ (2x + 3) / 2√(x^2 + 3x) ]

Using the rule of d/dx(u/v) = [v*d/dx(u) - u*d/dx(v)] / v^2

d^2 y/dx^2 = [ 2√(x^2 + 3x) * d/dx(2x + 3) - (2x + 3) * d/dx(2√(x^2 + 3x)) ] / (2√x^2 + 3x)^2

= [ 2*(2√x^2 + 3x) - (2x + 3)(1/√(x^2 + 3x) * (2x + 3)) ] / 4(x^2 + 3x)

= [ 4√(x^2 + 3x) - (2x + 3)^2 / √(x^2 + 3x) ] / 4(x^2 + 3x)

= [ {4(x^2 + 3x) - (2x + 3)^2} / √(x^2 + 3x) ] / 4(x^2 + 3x)

= (4x^2 + 12x - 4x^2 - 9 - 12x) / (x^2 + 3x) * 4√(x^2 + 3x)

= - 9 / 4(x^2 + 3x)^3/2

Hence         d^2 y/dx^2 = - 9 / 4(x^2 + 3x)^3/2

And we also know that

x^2 + 3x = y^2

So put the value of x^2 + 3x in the answer, we get

- 9 / 4(y^2)^3/2

- 9 / 4(y^2*^3/2)

- 9 / 4(y^3)

- 9 / 4y^3

Hence

Sep 22nd, 2015

There was a mistake and I corrected it in above. Okay???

Sep 22nd, 2015

Thats fine, thank you so much!

Sep 22nd, 2015

My Pleasure!!!

Sep 22nd, 2015

...
Oct 3rd, 2015
...
Oct 3rd, 2015
Sep 21st, 2017
check_circle